2015
DOI: 10.1111/1759-7714.12224
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the role of postoperative radiation therapy in patients with pIIIaN2 non‐small cell lung cancer: A propensity score matching analysis

Abstract: BackgroundReappraisal of the role of postoperative radiotherapy in pN2 non-small cell lung cancer (NSCLC) patients according to N1 lymph node involvement.MethodsA total of 218 pIIIa-N2 NSCLC patients who underwent complete surgical resection with systematic nodal dissections were enrolled. Propensity scores were used for matching N1 involvement. Overall survival (OS) and disease-free survival (DFS) were analyzed retrospectively.ResultsAfter matching, pN2b patients without N1 involvement (pN0N2b) exhibited bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Sixteen studies met the inclusion criteria but 6 were excluded because reported data did not allow extraction of comparison survival outcomes for the groups of interest 21 , 22 , 23 , 24 , 25 , 26 ( Figure 1 ). The 10 remaining studies 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 included 3 prospective studies, including 2 randomized controlled trials addressing the specific question of this meta-analysis, 4 retrospective studies, and 3 national database analyses, giving a pooled dataset of 18,077 patients (5453 [30.2%] receiving PORT and 12,624 [69.8%] without). Characteristics of included studies are shown in Table 1 , with resection type, chemotherapy regimens, and radiotherapy details summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixteen studies met the inclusion criteria but 6 were excluded because reported data did not allow extraction of comparison survival outcomes for the groups of interest 21 , 22 , 23 , 24 , 25 , 26 ( Figure 1 ). The 10 remaining studies 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 included 3 prospective studies, including 2 randomized controlled trials addressing the specific question of this meta-analysis, 4 retrospective studies, and 3 national database analyses, giving a pooled dataset of 18,077 patients (5453 [30.2%] receiving PORT and 12,624 [69.8%] without). Characteristics of included studies are shown in Table 1 , with resection type, chemotherapy regimens, and radiotherapy details summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies provided Kaplan–Meier estimates of DFS comparing PORT with no PORT. 27 , 31 , 33 , 35 , 36 Median DFS ranged from 16.8 to 25.5 months in the no-PORT groups and 25.8 to 33.7 months in the PORT groups. PORT significantly improved DFS at 1 year (n = 676; HR, 0.733; 95% CI, 0.414-1.052, P < .0001), 3 years (n = 676; HR, 0.732; 95% CI, 0.566-0.898; P < .0001) and 5 years (n = 639; HR, 0.735; 95% CI, 0.589-0.880; P < .0001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have applied PSM methods to divide patients into targeting groups and control groups, similar to randomized clinical trials. For example, a family history of lung cancer [2], postoperative radiotherapy [3], the use of betablockers [4], preoperative radiotherapy [5], intermittent chest tube clamping [6], systematic lymph node dissection and lobe-specific lymph node dissection [7], as well as other variables [8][9][10][11][12], have been used to divide patients into the two groups. Most cancer studies estimate survival curves as related to the N-years survival rate as their main outcome.…”
Section: Introductionmentioning
confidence: 99%